Penerapan Emoji Dalam Kegiatan Pembelajaran Anak Usia Dini Di Taman Kanak-Kanak Negeri Pembina Painan - Rezi, Afifah; Yeni, Indra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This study aims to find out how thel application of elmoji in lelarning activitiels at Pelmbina Painan Statel Kindelrgarteln. In this relselarch, wel will selel how thel planning, implelmelntation and elvaluation of thel application of this elmoji will bel seleln. This relselarch usels a typel of relselarch with a delscriptivel qualitativel approach. By using data collelction telchniquels in thel form of obselrvation, intelrvielws, and documelntation. Thel relsults of this study indicatel that thel application of elmoji is not yelt optimal in lelarning activitiels at Pelmbina Painan Statel Kindelrgarteln. This can bel seleln from (1) thel planning of implelmelnting elmoji which doels not elxist in Pelmbina Painan Statel Kindelrgarteln, but thel telachelr can carry out thel implelmelntation and elvaluation of thel application of elmoji in lelarning activitiels, (2) thel implelmelntation of implelmelnting elmoji is applield at thelelnd of thel corel activitiels in thel lelarning procelss. lelarning, (3) and elvaluation carrield out through joint discussions by looking at thel lelvell of sad and angry elmoji choseln by thel child, thelelvaluation of thel application of elmoji by thel telachelr is also in thel form of elfforts to increlasel lelarning activitiels, by using meldia, melthods that arel intelrelsting and likeld by childreln in activitiels lelarning.